Clinical Practice: Helicobacter pylori infection in childhood - ERTEM ŞAHİNOĞLU, DENİZ (SPRINGER, 2013)
Helicobacter pylori infection is recognised as a cause of gastritis and peptic ulcer disease (PUD) and usually acquired during the first years of life. While there is a decline in the prevalence of H. pylori infection in northern and western European countries, the infection is still common in southern and eastern parts of Europe and Asia. Symptoms of H. pylori-related PUD are nonspecific in children and may include epigastric pain, nausea and/or vomiting, anorexia, iron deficiency anaemia and hematemesis. Besides, only a small proportion of children develop symptoms and clinically relevant gastrointestinal disease. H. pylori infection can be diagnosed either by invasive tests requiring endoscopy and biopsy or non-invasive tests including the C-13-urea breath test, detection of H. pylori antigen in stool and detection of antibodies in serum, urine and saliva. The aim of treatment is at least 90 % eradication rate of the bacteria, and a combination of two antibiotics plus a proton pump inhibitor has been recommended as first-line treatment. However, frequent use of antibiotics during childhood is associated with a decline in eradication rates and the search for new treatment strategies as well. This is an overview of the latest knowledge and evidence-based guidelines regarding clinical presentation, diagnosis and treatment of H. pylori infection in childhood.
Keywords: Helicobacter pylori; Prevalence; Abdominal pain; Peptic ulcer disease; Diagnosis; Treatment; IRON-DEFICIENCY ANEMIA; PUBLIC-HEALTH IMPLICATIONS; STOOL ENZYME-IMMUNOASSAY; GASTRIC-CANCER; CLARITHROMYCIN RESISTANCE; ANTIBIOTIC-RESISTANCE; CONSENSUS REPORT; RISK-FACTORS; BREATH TEST; HONG-KONG